Does Fiscal Federalism Deter or Spur Secessionist Movements? Empirical Evidence from Europe. Issue 2 (23rd October 2017) - Rode, Martin; Pitlik, Hans; Borrella Mas, Miguel A´ngel
Abstract: Popular and scientific contributions often call for increased regional decision-making power to manage secessionist conflict, assuming that fiscally federalized countries are less prone to disintegrate politically. From a theoretical standpoint this is not clear though, as federalism creates an institutional paradox where autonomous legislative and bureaucratic structures can potentially be used to make secessionism a viable strategy in the first place. In particular, the role of asymmetric territorial arrangements in this association is crucially underexplored at present. Using electoral data on separatist political movements from a large variety of European regions since the mid-1990s, our findings indicate that regions with comparatively higher fiscal and institutional autonomy are more prone to vote for secessionist parties. Accounting for possible endogeneity, asymmetric territorial self-governance seems to cause much stronger incentives to vote for secessionist platforms, while the association with fiscally more symmetric arrangements is surprisingly small.